2001
DOI: 10.1111/j.1469-7793.2001.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological analysis of the negative chronotropic effect of endothelin‐1 in rabbit sinoatrial node cells

Abstract: 1. Electrophysiological effects of endothelin-1 (ET-1) were studied in rabbit sinoatrial node (SAN) using conventional microelectrode and whole-cell voltage and current recordings. 2. In rabbit SAN, RT-PCR detected ET(A) endothelin receptor mRNA. ET-1 (100 nM) increased the cycle length of action potentials (APs) from 305 +/- 15 to 388 +/- 25 ms; this effect was antagonised by the ET(A) receptor-selective antagonist BQ-123 (1 microM). ET-1 increased AP duration (APD50) by 22%, depolarised the maximum diastolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 68 publications
4
24
0
Order By: Relevance
“…The change in action potential waveform produced by efonidipine was very similar to that by 40 µM nickel, which specifically inhibits T-type Ca 2+ channels in myocardial cells (4,29). Similar change in action potential waveform was observed after application of mibefradil (40) and after application of efonidipine to isolated sino-atrial node cells (41) (42). Voltage clamp exeriments with isolated guinea-pig ventricular cardiomyocytes showed that efonidipine inhibits both L-type and T-type Ca 2+ channels concentration-dependently (30).…”
Section: Casupporting
confidence: 63%
“…The change in action potential waveform produced by efonidipine was very similar to that by 40 µM nickel, which specifically inhibits T-type Ca 2+ channels in myocardial cells (4,29). Similar change in action potential waveform was observed after application of mibefradil (40) and after application of efonidipine to isolated sino-atrial node cells (41) (42). Voltage clamp exeriments with isolated guinea-pig ventricular cardiomyocytes showed that efonidipine inhibits both L-type and T-type Ca 2+ channels concentration-dependently (30).…”
Section: Casupporting
confidence: 63%
“…Data from patients with angina pectoris have shown left bundle-branch block to be associated with raised ET-1 levels, suggesting that the hormone may be involved in conduction abnormalities [20]. Consistent with an ability of ET-1 to exert a direct effect on the pacemaker-conduction system, experiments on cells isolated from the rabbit SAN have demonstrated that ET-1 produces a negative chronotropic effect that is associated with direct ion channel modulation [21][23]. By contrast, to our knowledge, there is no current information available concerning direct effects of this peptide hormone on the AVN.…”
Section: Introductionmentioning
confidence: 94%
“…After stabilization of the amplitude of the signal (30 seconds to 1 minute), APs were recorded during 1 minute at a stable heart rate. APs were detected and analyzed, as previously described, 24 using MATLAB (The MathWorks, Inc., Natick, MA) for AP plateau amplitude and action potential at 50% re-polarization from the plateau level (termed action potential duration, APD). Time zero for computing APD was taken at the time of maximum up-stroke velocity of the AP.…”
Section: Monophasic Ap Recordingmentioning
confidence: 99%